1999
DOI: 10.1159/000029736
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Pallidal Stimulation in Cervical Dystonia

Abstract: Cervical dystonia (spasmodic torticollis) is a focal dystonia of the cervical region. Various treatment modalities have been performed with variable success rates. We present a 42-year-old woman complaining of involuntary head rotation for the last 3 years. Different medical treatments had been used for 3 years. Botulinum toxin injections resulted in temporary and moderate improvement for periods of 3–4 months. Pallidal stimulation was performed using a quadripolar electrode and a battery-operated programmable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 8 publications
(9 reference statements)
2
35
0
2
Order By: Relevance
“…Taken together several groups have described a significant pain reduction and an approximately 50% motor benefit in patients treated for severe cervical dystonia by bilateral pallidal stimulation. [23][24][25] In a patient with Meige syndrome, bilateral pallidal stimulation was able to further improve the condition after staged bilateral thalamotomy performed 10 years before.…”
Section: Treatment Resultsmentioning
confidence: 98%
“…Taken together several groups have described a significant pain reduction and an approximately 50% motor benefit in patients treated for severe cervical dystonia by bilateral pallidal stimulation. [23][24][25] In a patient with Meige syndrome, bilateral pallidal stimulation was able to further improve the condition after staged bilateral thalamotomy performed 10 years before.…”
Section: Treatment Resultsmentioning
confidence: 98%
“…3, 9]. I˙şlekel et al [18] suggested that the DBS target must be the GPi contralateral to the contracted sternocleidomastoid muscle. However, we found that ipsilateral DBS had the greatest beneficial effect in our patient with horizontal torticollis.…”
Section: Discussionmentioning
confidence: 99%
“…Fokale,gegenüber Botulinumtoxin resistente zervikale Dystonien zeigten nach den Ergebnissen anderer Gruppen eine signifikante Schmerzreduktion und eine Verbesserung der Motorik um etwa 50% unter bilateraler Pallidumstimulation [4,26,30], ein bei Meige-Syndrom 10 Jahre zuvor bilateral thalamotomierter Patient wies eine zusätzliche Besserung unter Pallidumstimulation auf [38].…”
Section: Sekundär Generalisierte Dystonienunclassified